Immunomodulation and Intestinal Morpho-Functional Aspects of a Novel Gram-Negative Bacterium Rouxiella badensis subsp. acadiensis - Yahfoufi, Nour; Alsadi, Nawal; Mallet, Jean Francois; Kulshreshtha, Garima; Hincke, Maxwell; Ismail, Nafissa; Matar, Chantal (Frontiers in Microbiology, 2021)
Novel probiotics candidates of the plant ecosystem are now considered part of the next-generation probiotics (NGPs). We have isolated a novel bacterium (Serratia vaccinii) from the biota of wild blueberry fruit. In order to establish the probiotic potential of the bacterium, several in vitro properties were assessed along with in vivo beneficial health effect evaluation in Balb/c mice. We investigated the strain antibiotic susceptibility and tolerance to gastric and intestinal environment, as well as its ability to attach to human intestinal epithelial cells (Caco-2 and HT-29). In addition, Balb/c mice were used to explore the immune-modulatory characteristics of the live bacterium at the intestinal level and its impact on the morpho-functional aspects of the intestinal mucosa. In vitro assays revealed the ability of S. vaccinii to survive the gastric and intestinal simulated conditions and to partially adhere to the human intestinal epithelial cells. The bacterium was shown to be sensitive to an array of antibiotics. Immuno-modulation studies with mice orally administered with S. vaccinii showed a higher number of IgA positive cells in the small intestine, a higher concentration of the anti-inflammatory cytokine IL-10 in the intestinal mucosa, as well as an increase in the number of goblet cells. The anti-inflammatory cytokine miR146a was found to be increased in the ileum and brain. Taken together, these findings indicate that treatment with the investigated bacterium can have beneficial health effects on homeostasis of immune response and intestinal. Our study indicated that S. vaccinii strain presents favourable strain-specific properties for its utilization as functional food and opens the doors to potential health benefits that require further investigations.